Religiosity in Banyumas Folklore as Children's Literacy Material Primary School - Detria Nur Aini Sutrisno; St.Y. Slamet; Septi Yulisetiani (Proceeding International Conference on Religion, Science and Education, 2023)
Folklore material in elementary schools has an important role in the values contained in stories for students, especially religious values. This study aims to describe the facts of the story in terms of the religious values of the main character in Banyumas folklore which are good for being used as material for children's literacy. The type of research used in this study is qualitative research with descriptive methods. The source of the data in this study was the folklore of Banyumas by Kurnianto, et al entitled “Cerita Rakyat Jawa Tengah. Some of the story titles taken include the Kadipaten Penyarang, Santri Undig Membunuh Burung Garuda Beri dengan Pusaka Tilam Upih, Babad Pasir Luhur, Baturraden, and Sepatnunggal”. The data collection technique used was library research or content analysis. The technique includes a series of stages of data reduction analysis, data presentation, and drawing conclusions. The results of the analysis show (1) the characters in the five stories are humble, wise, religious, and have a fighting spirit; (2) the religious values contained in the five stories show a religious relationship with God which is shown in their daily worship, involving God in every matter, asking for guidance, and praying every time they want to make a decision. The religious value with fellow human beings shown in the story is the character of the main character who is humble and helps between fellow human beings and does not discriminate in providing assistance.